House of concepts : design academy Eindhoven. - Schouwenberg, Louise, ....-; Staal, Gert, 1956- (Amsterdam : Frame, 2008)
Dutch design is held in high esteem around the world. Its favourable international reputation is based on the work of many designers including Jurgen Bey, Hella Jongerius and Maarten Baas, who all have one thing in common: Design Academy Eindhoven. Design Academy Eindhoven is the Netherlands' leading institution for developing design talent and it has produced a veritable who's who of the country's creative scene. The final projects of its graduates often attract international attention; their annual presentation has become a must-see for innovative companies, brands and designers from around the world. House of Concepts presents the legendary school that was founded as the Academy for Industrial Design Eindhoven sixty years ago. It contains outstanding original work created in a top-quality educational environment that emphasises practical skills rather than theory. The book not only features Design Academy Eindhoven graduates and their work, but also gives insight into the conceptual design for which the Netherlands is famous. House of Concepts also includes extensive interviews with renowned alumni such as Jurgen Bey, Richard Hutten, Joris Laarman and Judith de Grauw as well as Jeroen and Joep Verhoeven.
Keywords: Ontwerpen